A broad band energy harvesting rectenna based on metamaterial complementary split ring resonator broadband antenna and BALUN rectifier. (July 2022) - Benayad, Ali; Tellache, Mohamed
Abstract: In this paper, we present a new design of a broadband energy harvesting rectenna. The rectenna consists of a compact bidirectional complementary split ring resonator broadband antenna and a broadband Balanced to unbalanced rectifier. The antenna design offers a 60% size reduction comparing to the conventional designs. The realized rectenna operates at a large bandwidth that includes four main harvestable ambient frequency bands (GSM-1.8 GHz, UMTS-2.1 GHz, WiFi-2.45 GHz and 4G-2.6 GHz GSM). The prototypes have been printed on 1.58 mm thickness FR4 substrate with a permittivity of 4.3. The design shows a higher efficiency compatibility at the lower power levels where it has reached 72% at −6 dBm input power.